Prognostic role of platelet to lymphocyte ratio in prostate cancer: A meta-analysis - Wang, Jiangfeng (Medicine (Baltimore), 2018)
BACKGROUND: Recently, the prognostic value of the platelet-to-lymphocyte ratio (PLR) has been identified in multiple cancers. However, the prognostic significance of the PLR in prostate cancer (PCa) remains conflicting. We therefore searched relevant studies and conducted a meta-analysis. METHODS: Papers from the databases of PubMed, Web of Science, and the Cochrane Library were retrieved. Six studies comprising 1324 patients were included. RESULTS: The pooled analysis demonstrated that an elevated PLR predicted poor overall survival (OS; HR = 1.85, 95% CI = 1.51–2.25, P < .001) and disease-free survival (DFS; HR = 1.4, 95% CI = 1.1–1.79, P = .007). Subgroup analyses showed that the PLR remained a significant prognostic factor for OS irrespective of ethnicity, tumor stage, or cut-off value. The PLR was an indicator of poor DFS in Asian patients, but not in Caucasian patients. No significant publication bias was detected. CONCLUSION: This meta-analysis showed that a high PLR was correlated with poor DFS and OS in patients with prostate cancer. Due to this meta-analysis being derived from a few studies, the results should be validated in clinical practice.